ACADEMICIAN KORZH O.O. IS AN OUTSTANDING SCIENTIST OF THE XX CENTURY, FOUNDER OF A NEW STAGE OF DEVELOPMENT OF ORTHOPEDICS AND TRAUMATOLOGY IN UKRAINE (TO THE 100TH ANNIVERSARY OF HIS BIRTH) - Tankut, Volodymyr; Filipenko, Volodymyr; Golubeva, Inna; Shevchenko, Olena; Berenov, Kostyantyn (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2024)
The article is dedicated to academician Korzh Oleksii Oleksandrovych.